A human adenovirus encoding IFN-γ can transduce Tasmanian devil facial tumour cells and upregulate MHC-I. (16th November 2022) - Kayigwe, Ahab N.; M. Darby, Jocelyn; Lyons, A. Bruce; L. Patchett, Amanda; Lisowski, Leszek; Liu, Guei-Sheung; S. Flies, Andrew
Abstract : The devil facial tumour disease (DFTD) has led to a massive decline in the wild Tasmanian devil ( Sarcophilus harrisii ) population. The disease is caused by two independent devil facial tumours (DFT1 and DFT2). These transmissible cancers have a mortality rate of nearly 100 %. An adenoviral vector-based vaccine has been proposed as a conservation strategy for the Tasmanian devil. This study aimed to determine if a human adenovirus serotype 5 could express functional transgenes in devil cells. As DFT1 cells do not constitutively express major histocompatibility complex class I (MHC-I), we developed a replication-deficient adenoviral vector that encodes devil interferon gamma (IFN-γ) fused to a fluorescent protein reporter. Our results show that adenoviral-expressed IFN-γ was able to stimulate upregulation of beta-2 microglobulin, a component of MHC-I, on DFT1, DFT2 and devil fibroblast cell lines. This work suggests that human adenoviruses can serve as a vaccine platform for devils and potentially other marsupials.